The Neotropical 'polymorphic earless praying mantises' – Part I: molecular phylogeny and revised higher‐level systematics (Insecta: Mantodea, Acanthopoidea). (July 2016) - RIVERA, JULIO; SVENSON, GAVIN J.
Abstract: We perform phylogenetic analyses of the 'polymorphic earless praying mantises', a heterogeneous assemblage comprising c. 55% of mantodean diversity in the Neotropics. Bayesian and maximum‐likelihood were implemented on a DNA dataset of 9949 aligned nucleic acid characters comprising ten mitochondrial and nuclear genes. Our analyses largely resolved congruent relationships with high levels of support for higher‐level taxonomic groups, but revealed extensive inconsistencies between the resolved topology and morphology‐based classification systems. The polymorphic earless praying mantises, now granted superfamily status as the Acanthopoideastat. n., comprises 8 families, 15 subfamilies and 18 tribes. Our newly revised organization required the following taxonomic changes: (i) Thespidaesensu n., including subfamilies Pseudopogonogastrinaesubfam. n., Pseudomiopteryginaesensu n., Bantiinaesubfam. n., Miobantiinaesensu n. and Thespinaesensu n. (tribes Musoniellinitrib. n. and Thespinisensu n. ); (ii) Angelidaestat. n. etsensu n. ; (iii) Coptopterygidaestat. n. ; (iv) Liturgusidaesensu n. ; (v) Photinaidaestat. n., including Macromantinaestat. n., Cardiopterinaestat. n., Photiomantinaesubfam. n. and Photinainaesensu n. (tribes Microphotininitrib. n., Orthoderellinistat. n. and Photinainisensu n. ); (vi) Stenophyllidaestat. n. ; (vii) Acontistidaestat. n. ; and (viii) Acanthopidaesensu n. Our new system also resulted in the reassignment of various genera to new and existing higher‐level taxa, the exclusion of old world genera otherwise traditionally classified among the Thespidae, Liturgusidae and Angelidae, the confirmation of Stenophylla Westwood as member of this clade, and the revalidation of Paradiabantia Pizastat. r. We provide diagnoses for all suprageneric taxa using external morphological characters and male genitalia. A key to higher‐level groups is provided. We incorporate egg case structural variation as a novel approach for taxon delineation. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:29E37322‐30EB‐4F64‐80C9‐E2149B5B0195 .